1952
DOI: 10.1017/s0022149x00032600
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Examination of the Worm Egg Count Sampling Technique for Sheep

Abstract: The use of worm egg counts for observational and experimental purposes in naturally infested sheep has become very popular since Whitlock and Gordon (1989) introduced the simple and efficient McMaster slide technique. When using a dilution technique such as this, the accuracy of the count increases as more eggs are counted. In order to count more eggs when using the McMaster slide it is usually more convenient, in practice, to take more samples (i.e. count more cells) than to alter the dilution. It is therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1956
1956
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…The distribution of a parasite within a given habitat is also determined largely by its life cycle, resulting in either a random or clumped distribution of infected mammalian hosts in the relevant woodland areas. Lewis ( 1 9 6 8~) indicated that the frequency distribution of parasite numbers in Apodentus sylvaticus from Wales was represented by a negative binomial, which was confirmed in other hosts by Hunter & Quenouille (1952) and Williams & Harris (1965). Such a distribution, unlike a Poisson distribution, suggests that the infective stages tended to be aggregated or clumped rather than randomly distributed within a given habitat.…”
Section: Discussionmentioning
confidence: 85%
“…The distribution of a parasite within a given habitat is also determined largely by its life cycle, resulting in either a random or clumped distribution of infected mammalian hosts in the relevant woodland areas. Lewis ( 1 9 6 8~) indicated that the frequency distribution of parasite numbers in Apodentus sylvaticus from Wales was represented by a negative binomial, which was confirmed in other hosts by Hunter & Quenouille (1952) and Williams & Harris (1965). Such a distribution, unlike a Poisson distribution, suggests that the infective stages tended to be aggregated or clumped rather than randomly distributed within a given habitat.…”
Section: Discussionmentioning
confidence: 85%
“…In that case the spacing of repeated observations would be of importance. An aspect of this problem is treated by Hunter & Quenouille (1952)]. Although a greater body of data would be required to produce accurate estimates, it is evident from an inspection of Table 4 that the unrelated calves approach their theoretical maximum efficiency much more rapidly than the twins.…”
Section: Methodsmentioning
confidence: 99%
“…Southwood (1966) explains that k values derived from animal population sampling are often in the region of 2; when higher they denote less clumping and when lower they denote more, these trends leading the negative binomial respectively towards the Poisson and the logarithmic series. Table VI shows k values (k 0 of Southwood, 1966) all of less than 0-5, illustrating the high degree of clumping characteristic of parasitic populations (vide Hunter & Quenouille, 1952;Crofton, 1971a, b).…”
Section: Description and Interpretation Of Infestation Frequency Distmentioning
confidence: 98%